Influence of Parents’ Socio-Economic Status on Academic Performance among Public Secondary School Students in Cross River State, Nigeria - EJALE; Ondah Jacob; OKORIE; Agnes Ojobo; ABDULLATIF; Murtala (Federal University Gusau Faculty of Education Journal, 2026)
This study was carried out to examine the “Influence of Parents’ Socio-Economic Status on Students’ Academic Performance in Public Secondary Schools in Cross River State, Nigeria”. One objective of the study focused on; influence of parents’ economic status on students’ academic performance in public secondary schools in Cross River State, Nigeria and the research question and null hypothesis were in line with the objective of the study. The population for this study is 87,071 comprising of all principals’, teachers, students of public secondary schools in Cross River State. Three hundred and eighty-two (382) respondents were sampled to represent the total population. Out of the distributed copies of the questionnaire, three hundred and seventy-five (375) copies of questionnaire were retrieved. Descriptive survey was used for the study. One instrument was employed to collect data for the study. The research instrument was validated by three experts through face and content validity. The reliability index shows .783 using Cronbach Alpha for its analysis. Descriptive statistics was used to answer research question and ANOVA was used in testing the hypothesis. The findings of the study reveal that parents with stable or average socioeconomic status significantly enhance students’ academic performance in public secondary schools across the state. The economic status of parents was found to determine students’ ability to participate in both curricular and extracurricular activities. The study concludes that, parents’ economic status plays a critical role in shaping students’ academic outcomes among other. The study recommends that: parents, government, and NGOs should provide financial support and educational assistance to children from low-income families through scholarships, free textbooks, and school meal programs.